Correlation studies between structural and ionic transport properties of Lithium‑Ion hybrid gel polymer electrolytes based PMMA‑PLA - Norfatihah, Mazuki; Mohd Zieauddin, Kufian; Nagao, Yuki; Ahmad Salihin, Samsudin (Springer New York LLC, 2022)
In this work, an investigation on hybrid gel polymer electrolytes (HGPEs) comprising of polymethyl methacrylate (PMMA)-polylactic acid (PLA) incorporated with lithium bis(trifuoromethanesulfony)imide (LiTFSI) was carried out. The HGPEs samples were characterized for their structural, thermal and ionic conduction properties via FTIR, XRD, DSC, and EIS. FTIR analysis showed the interaction between the PMMA-PLA hybrid polymer and LiTFSI through the appearance of peaks and peak shifts at the coordinating site on the polymer blend. The DSC analysis showed that the glass transition temperature (Tg) of HGPEs was decreased as the LiTFSI content increased, suggesting that the ion–dipole interaction decreased and led to the enhancement of the HGPEs system’s amorhous phase. The ionic conductivity was calculated based on the Cole–Cole plot and the incorporation of 20 wt% LiTFSI into the hybrid polymer matrixes revealed that the maximum ionic conductivity was 1.02 × 10–3 S cm−1 at room temperature as the amorphous phase increased. The dissociation of ions and transport properties of the PMMA-PLA-LiTFSI systems was determined via the dielectric response approach and it was found that number density (ɳ), mobility (μ), and diffusion coefficient (D) of mobile ions followed the ionic conductivity trend.